A study on circular economy adoption in Indian MSMEs: exploring the circular economy practices in large industry - Garg, Anamika; Sharma, Renuka; Saini, Chand P (Journal of Social Review and Development, 2025)
The existing linear economics system has been unsustainable whereby a lot of waste is produced and the natural resources are not utilized efficiently. To combat that, the Circular Economy (CE) has been presented as a universal option that will be regenerative and restorative, plus sustainable. To the Indian industrial environment and specifically the Micro, Small and Medium Enterprises (MSMEs), circular economy offers a new transformative paradigm in the realization of long term sustainability. To gain better insight in successful strategies and implementation techniques, this study also comprises an analysis of the case of the Reliance Industries, which is one of the largest conglomerates in India and has implemented such strategies related to CE approaches as efficient use of resources and reduction of waste. Findings suggest that Enablers and Barriers to CE adoption are the most frequently mentioned topics in the literature. Though there is a growing interest in adoption of CE practices by MSMEs in India, there are still various challenges which bedevil broad adoption of the practice. These are; low awareness, lack of finances and poor policy and regulation support. Considering both general trends and the micro-level of business operations, this paper will be implemented into the existing discussion on sustainable development and will highlight the crucial place of MSMEs in the shift toward the states of circular economy in India.